A Large Mandibular Anterior Swelling—A Diagnostic Dilemma: A Case Report - Sonar, Prasanna R.; Panchbhai, Aarati S.; Dangore, Suwarna B. (European Journal of General Dentistry, 2024)
Hybrid lesions are lesions that combine characteristics of many pathologies. The literature has shown a rare relationship between aneurysmal bone cysts, fibro-osseous lesions, and a central giant cell lesion. In this case, we describe an unusual hybrid lesion in the mandibular anterior area. As a result, the goal of this article is to highlight the significance of comprehensive clinical, radiographic, and histological investigation in addition to presenting a rare instance of hybrid lesion. This will lessen the likelihood of misdiagnosis in these situations and aid in prompt treatment planning of the lesion.
Keywords: hybrid lesions; aneurysmal bone cysts; ossifying fibroma; central giant cell granuloma